Gelatin-based biomaterials and gelatin as an additive for chronic wound repair - Cao, Hongwei; Wang, Jingren; Hao, Zhanying; Zhao, Danyang (Frontiers in Pharmacology, 2024)
Disturbing or disrupting the regular healing process of a skin wound may result in its progression to a chronic state. Chronic wounds often lead to increased infection because of their long healing time, malnutrition, and insufficient oxygen flow, subsequently affecting wound progression. Gelatin-the main structure of natural collagen-is widely used in biomedical fields because of its low cost, wide availability, biocompatibility, and degradability. However, gelatin may exhibit diverse tailored physical properties and poor antibacterial activity. Research on gelatin-based biomaterials has identified the challenges of improving gelatin's poor antibacterial properties and low mechanical properties. In chronic wounds, gelatin-based biomaterials can promote wound hemostasis, enhance peri-wound antibacterial and anti-inflammatory properties, and promote vascular and epithelial cell regeneration. In this article, we first introduce the natural process of wound healing. Second, we present the role of gelatin-based biomaterials and gelatin as an additive in wound healing. Finally, we present the future implications of gelatin-based biomaterials.